Beep! Beep! - Sirett, Dawn; Harvey, Victoria; Palastanga, Victoria (London Dorling Kindersley, 2012)
Help your baby discover all about tractors, trucks and rockets with touch and feel textures. "Baby Touch and Feel Beep! Beep!" is full of twinkly, bumpy, scaly, silky, sandy, sticky and shiny textures in a chunky package. Encourage your baby to learn early concepts such as colours, shapes and patterns as they turn each page. See the big strong bulldozer at work, the long arm of the digger and high in the sky - it's a plane! This title is perfect for encouraging tiny fingers to explore and young minds to develop. Sturdy pages with rounded corners mean "Baby Touch and Feel Beep! Beep!" will provide years of enjoyment
Picture Book
1 2 23
Keywords: Motor vehicles -- Juvenile fiction; Textured books -- Specimens